The Influence of Entrepreneurial Motivation on MSME Business Success: A Literature Review - Ana Rahmawati; Nanang Setiawan (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The issues of poverty, unemployment, and income inequality pose serious challenges to governments across various countries, influenced not only by economic factors but also by sociocultural aspects and the availability of human resources. This research aims to explore the role of entrepreneurial motivation and its impact on the success of Micro, Small, and Medium Enterprises (MSMEs) through a comprehensive literature review. The study identifies four critical stages in the entrepreneurial process—preparation, implementation, maintenance, and business development. Each stage requires strong motivation and in-depth analysis of the conditions faced by MSMEs. By analyzing relevant literature, this research provides new insights for MSME entrepreneurs to manage their businesses more effectively in pursuit of economic sustainability. The primary contribution of this research is to highlight the importance of entrepreneurial motivation as a catalyst for MSME development and an effective strategy in supporting local and national economic growth. By enhancing understanding of the factors influencing MSME success, this study aims to provide a foundation for public policies that support sustainable development in the MSME sector